1992
DOI: 10.2337/diacare.15.11.1631
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Adults with Diabetes

Abstract: Depression in diabetes is a prevalent and chronic condition. The etiology is unknown but is probably complex; and biological, genetic, and psychological factors remain as potential contributors. Several neuroendocrine and neurotransmitter abnormalities common to both depression and diabetes have been identified, adding to etiological speculations. Pharmacotherapy of depression may improve both mood and glucose regulation in diabetes, although controlled studies of the efficacy of psychotherapy and pharmacother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0
15

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(180 citation statements)
references
References 0 publications
4
161
0
15
Order By: Relevance
“…Studies also repeatedly have found that the course of depression is more severe in diabetes, with high relapse rates following initial episodes and a protracted period of recovery in both children and adults Kovacs, Goldston, Obrosky, & Bonar, 1997;Lustman, Griffith, & Clouse, 1997;Lustman, Clouse, & Alrakawi, 1997). The problem of underdiagnosis of depression in patients with diabetes is significant, with as many as 2 of 3 cases remaining undetected, primarily because many symptoms of depression (e.g., fatigue) are also symptoms of diabetes (Lustman, Griffith, & Clouse, 1997). Depression is associated with many health behaviors that have a negative impact on diabetes management and metabolic control such as smoking, alcohol and other drug abuse, and dysregulation in appetite and eating.…”
Section: Psychosocial Adjustment and Qolmentioning
confidence: 99%
“…Studies also repeatedly have found that the course of depression is more severe in diabetes, with high relapse rates following initial episodes and a protracted period of recovery in both children and adults Kovacs, Goldston, Obrosky, & Bonar, 1997;Lustman, Griffith, & Clouse, 1997;Lustman, Clouse, & Alrakawi, 1997). The problem of underdiagnosis of depression in patients with diabetes is significant, with as many as 2 of 3 cases remaining undetected, primarily because many symptoms of depression (e.g., fatigue) are also symptoms of diabetes (Lustman, Griffith, & Clouse, 1997). Depression is associated with many health behaviors that have a negative impact on diabetes management and metabolic control such as smoking, alcohol and other drug abuse, and dysregulation in appetite and eating.…”
Section: Psychosocial Adjustment and Qolmentioning
confidence: 99%
“…Although the specific mechanisms through which psychological stress c m effect diabetes mellitus are not well-known, stress has been linked to poor glycemic control (Cox & Gonder-Frederick, 1992), decreased exercise (Goetsch, Abel & Pope, 1994), and even to the onset of the illness, particularly in people with type 2 diabetes (Lustman, 1988;Rubin & Peyrot, 1992). The relationship between stress and diabetes is, however, reciprocal, with stress affecting diabetes mellitus, and diabetes mellitus affecting levels of stress (Cox & Gonder-Frederick 1992 As with anxiety, depression in people with diabetes may occur for severd different reasons, including in response to the psychosocial hardships of the disease, biological changes directly related to the condition, or from previous biological or genetic factors making the individual vulnerable to depression (Lustman et al, 1992 One of the difficulties in diagnosing depression in people with diabetes is that many of the symptoms of depression, such as weight loss, changes in appetite, and fatigue, are also syrnptoms of diabetes and its treatment (Lustman, Amado & Wetzel, 1983;Lustman et al, 1992 (Cox & Gonder-Frederick, 1992). Research in this area generally shows the use of active coping strategies to relate positively to glycemic control, and negatively to depression and anxiety (Maes, Leventhal & DeRidder, 1996).…”
Section: Psycholoaical Adiustment To Diabetes Mellitusmentioning
confidence: 99%
“…Entretanto, a prática tem mostrado que o diagnóstico da depressão no diabetes não é tão controverso como em outras condições médicas como, por exemplo, o câncer. Uma estratégia recomendada na literatura é a utilização de outros sintomas depressivos que não esses possivelmente decorrentes do diabetes 3 . …”
Section: Diagnóstico Da Depressão No Diabetesunclassified